Responses of herbaceous mimosa (Mimosa strigillosa), a new reclamation species, to soil pH - Nuruddin, Ahmad Ainuddin; Chang, Mingteh (1999)
Growth responses of herbaceous mimosa (Mimosa strigillosa Torr. and Gray), a potential new reclamation species in the SE USA and Mexico, to nine soil pH scales were studied under a controlled environment at Nacogdoches, TX, USA. Twenty seeds were planted in each of 40 (nine scales plus one control in four replicates) 20.3-cm pots filled with Tonkawa sandy soil. These pots were treated with H2SO4 or Ca(OH)2 to adjust each pot to its designated pH level. After 15 days of seeding, the emergence rate was at best about 50-70% for pH 4.7-6.6. The plant can survive and grow at soil pH as low as 4.7, but the optimum growth seems to be on soils with pH ranging from 6.2 to 7.1. At this pH range, the plant exhibits higher values of green and dry biomass, longer shoot growth and lower root/shoot weight and length ratios. The survival rate was greater than 90% for all treatments, except for pH 4.1. There were no nutrient deficiencies in plant tissues on soil pH 4.7 or higher. The plant allocated more growth to the shoot under optimum conditions, but more growth to the roots under environmental stress. It is not suitable for herbaceous mimosa to grow on soils with pH 4.1 or less.